Pemberdayaan Kelompok Nelayan melalui E-Commerce oleh Aruna Indonesia - Teta Riasih Teta Riasih; Lina Favourita Sutiaputri (Politeknik Kesejahteraan Sosial Bandung, 2022)
Empowerment is a way in which people, organizations, and communities gain control over their own lives, including for fishermen groups which consist of economic, social, and environmental empowerment which is the focus of this research. In Indonesia, the fisheries sector is a great opportunity for business people because it is one of the pillars of Indonesia's current economy. Aruna is a digital startup or startup that focuses on fisheries. The goal is to connect small fishermen throughout Indonesia directly to the market using technology assistance. This is a site for fishermen to be able to learn integrated fisheries management, find out about the latest fishery data and fishery online trading systems, apart from strengthening the economy, Aruna conducts social and environmental empowerment for improving the welfare of fishermen and their families. The research approach used is a qualitative approach, which describes the empowerment of fishermen groups by Aruna by using the technique of focus group discussion, interviews, and discussions with experts and informants consisting of fishermen, mira, community leaders, local heroes, management, and Aruna's founders, totaling 32 people. The results showed that overall the economic empowerment that has been carried out has been very good, but the social empowerment carried out by Aruna still has limitations, especially in the availability of human resources to empower the Nelyan community who require expertise as a local academic influencer, namely someone who has influence and can influence the audience to make a certain choice or action. People who have this ability are social workers who can become agents of change. So that in the future it is necessary to involve social workers to carry out social empowerment for fishing communities. Keywords: Empowerment, Groups, Fisherman, e-commerce